(untitled) (EAAE Annual Conference Proceedings, 2023)
If modernist architecture allowed for a continuous space between building and landscape, nurturing the understanding of the “forest edge as man’s ideal habitat and as a mythical image” (Geddes 1982), today the boundaries between the artificial and natural, the urban and the sylvan, are increasingly folding in.